Head Circumference Growth Function as a Marker of Neurological Impairment in a Cohort of Microcephalic Infants and Children - Coronado, Ricard; Giraldo, Jesús; Macaya, Alfons; Roig, Manuel (Neuropediatrics, 2012)
Our aim was to investigate the correlations between head circumference (HC) growth and neurological impairment in microcephalic patients.HC charts of 3,269 patients from a tertiary pediatric neurology section were reviewed and 136 microcephalic participants were selected. Standardized HC Minimum, HC Drop, and HC Catch-up variables were defined. Children with evidence of significant learning disability and/or significant cerebral palsy were classified within the neurologically impaired group and the rest of participants within the normal group.Using discriminant analysis, we found that HC Minimum and HC Drop were relevant markers of neurological impairment. A positive HC Catch-up was significantly linked to a better outcome although this variable did not add significant information to HC Minimum and HC Drop. A Fisher linear discrimination cutoff function (C-function) was obtained as C = HC Minimum + HC Drop with a cutoff level of C = –4.28 standard deviations (SD).In our cohort, the addition of the lowest HC z-score to the preceding HC z-score drop was below −4.28 SD in 6 out of 10 neurologically impaired patients , whereas in the normal group, the result was over −4.28 SD in 9 out of 10 participants.
Keywords: microcephaly; learning disability; cerebral palsy; discriminant analysis; growth and development